Ballistic propagation of density correlations and excess wall forces in quenched granular media - Schindler, Thomas; Rohwer, Christian M. (Physical Review E, 2020)
We investigate a granular gas in a shaken quasi-two-dimensional box in molecular dynamics computer simulations. After a sudden change (quench) of the shaking amplitude, transient density correlations are observed orders of magnitude beyond the steady-state correlation length scale. Propagation of the correlations is ballistic, in contrast to recently investigated quenches of Brownian particles that show diffusive propagation [Rohwer et al., Phys. Rev. Lett. 118, 015702 (2017)PRLTAO0031-900710.1103/PhysRevLett.118.015702, Rohwer et al., Phys. Rev. E 97, 032125 (2018)2470-004510.1103/PhysRevE.97.032125]. At sufficiently strong cooling of the fluid the effect is overlaid by clustering instability of the homogeneous cooling state with different scaling behavior. We are able to identify different quench regimes. In each regime correlations exhibit remarkably universal position dependence. In simulations performed with side walls we find confinement effects for temperature and pressure in steady-state simulations and an additional transient wall pressure contribution when changing the shaking amplitude. The transient contribution is ascribed to enhanced relaxation of the fluid in the presence of walls. From incompatible scaling behavior we conclude that the observed effects with and without side walls constitute distinct phenomena.
CRIS-Team Scopus Importer:2020-12-11